Foreign Fictions: ‘Research’ about Ethiopian Legal Reform in a Top-Tier Academic Journal - Cochrane, Logan (Journal of Sustainable Development Law and Policy, 2025)
Top tier academic journals claim to publish the most rigorous, peer reviewed research. This evidence based found therein is utilized to support decision making for sustainable development. In parallel, many journals that are published in the Global South are accused of CFJOH MPXFS RVBMJUZ PS EJTSFHBSEFE BT kQSFEBUPSZl 5IJT BSUJDMF FYQMPSFT BO FYBNQMF PG B kGPSFJHO GJDUJPOl written about Ethiopia and published in a top tier academic journal. The narratives and evidence from that top tier journal are contrasted with research published in Ethiopian journals. This case study shows that Ethiopian scholars have produced important research and contributed evidence, but have largely been ignored, or silenced, perpetuating foreign fictions. This is important because policy and law seeking to enable development are informed and influenced by the research produced in top tier journals. Based upon this, this BSUJDMF DSJUJRVFT BTTVNQUJPOT BCPVU mUPQ UJFSn KPVSOBMT BT XFMM BT UIPTF BCPVU &UIJPQJBO journals, and further about the continued colonial power imbalances that exist within knowledge production systems. This has implications for universities and scholars, which continue to privilege a particular set of journals that are largely based in the Global North and wherein contributing authors are also largely based in the Global North. The reproduction of colonial relationships within global knowledge production systems calls for much broader critical reflection about whose voices are privileged as authentic conveyors of knowledge and how these privileges are institutionalized.